CHEMICAL CONTROL OF MOSS AND EPIPHYTIC WEEDS ON PRUNED SEEDLING TEA PLANTS: EFFECTIVENESS, PHYTOTOXICITY, AND ECONOMIC ANALYSIS - Ahmad Ghozali Ardiansyah; Gina Nur’aini Buchory; Fani Fauziah (UIN Sunan Gunung Djati Bandung, 2026)
Moss and epiphytic weeds colonizing pruned tea (Camellia sinensis) stems impede shoot regeneration and increase production costs through labour-intensive manual removal. This study evaluated three chemical treatments, (A) herbicide ammonium glufosinate (5 ml/L) + sticker; (B) soda ash (30 kg/ha) + lime (40 kg/ha); and (C) fungicide (1 kg/ha), against (D) an untreated control, using a randomized complete block design with six replications across 24 plots (25 m² each) at Tea Plantation, West Java, from August to December 2025. Parameters assessed included moss and weed dry biomass, shoot count, shoot height, relative shoot elongation rate (RSER), phytotoxicity, and cost per hectare. All chemical treatments significantly reduced moss and weed biomass at 2–4 weeks after application (WAA), with biomass shrinkage of 66–71%. Efficacy declined by 8 WAA coinciding with increased rainfall (197.5 mm), confirming the transient nature of chemical suppression under humid highland conditions. Treatment B caused visible phytotoxicity, leaf blackening and white surface deposits, making it unsuitable for routine application. The untreated control produced the highest shoot count (236 shoots; significantly greater than treatments A and B), while absolute final shoot height at 112 DAA was numerically greatest in Treatment C (17.25 cm vs. 15.35 cm in the control), although the corresponding shoot height increment did not differ significantly among treatments (13.20–15.31 cm); Treatment B recorded the significantly highest RSER (0.033 day⁻¹) relative to the control (0.024 day⁻¹), though A and C were not significantly distinguishable from either. Economic analysis revealed fungicide as the most cost-efficient option at IDR 213,833/ha, compared to IDR 265,333/ha (A) and IDR 544,333/ha (B).